2018
DOI: 10.1055/s-0038-1636910
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Ligament Knee Injuries

Abstract: The posterior cruciate ligament (PCL)-based multiple ligament injury, or dislocated knee, is often part of a multisystem injury complex that not only includes the knee ligaments, but may also include blood vessels, skin, nerves, fractures, and other organ system trauma. These factors must be considered in the scope of treating this complex knee injury. These complex knee ligament injuries can result in significant functional instability for the affected individual. This article will discuss multiple ligament k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
(61 reference statements)
0
9
1
2
Order By: Relevance
“…Data for the secondary outcomes analyzed in the present study also compare favorably to previous reports. While the incidence of persistent instability after MLKI reconstruction has been previously reported to range from 18 to 100% (mean=42%), 3 9 persistent instability was noted in only 12% of cases in the present study with at least 1 year of follow-up. Three of these (9.5%) had varus and/or rotational instability and patients underwent successful revision of the PLC component of KD IV reconstructions, and two of these revisions included realignment tibial osteotomies.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Data for the secondary outcomes analyzed in the present study also compare favorably to previous reports. While the incidence of persistent instability after MLKI reconstruction has been previously reported to range from 18 to 100% (mean=42%), 3 9 persistent instability was noted in only 12% of cases in the present study with at least 1 year of follow-up. Three of these (9.5%) had varus and/or rotational instability and patients underwent successful revision of the PLC component of KD IV reconstructions, and two of these revisions included realignment tibial osteotomies.…”
Section: Discussioncontrasting
confidence: 63%
“…Multiligamentous knee injury (MLKI) is relatively uncommon, but can cause significant functional impairment and devastating long-term sequelae, such as persistent pain and instability, inability to return to previous activities, decreased range of motion (ROM), and post-traumatic osteoarthritis (PTOA). 1 2 3 Surgical treatment of MLKI has been reported to yield better functional outcomes in short- to medium-term follow-up in comparison with conservative treatment. Based on patient-reported outcomes in conjunction with assessments of knee stability and ROM, surgical reconstruction for MLKIs has been recommended over repair.…”
mentioning
confidence: 99%
“…Dessa maneira, a luxação do joelho deve ser avaliada em todo paciente que apresenta lesão em dois ou mais ligamentos desta articulação. 2 3 5 6 7 8 9 10…”
Section: Introductionunclassified
“…A gravidade dessas lesões vasculares está enfatizada pelo fato de que, independentemente do tratamento, a incidência de amputações nesses pacientes é de 12% dos casos. 3 6 8 9 12 14…”
Section: Introductionunclassified
“…In fact, ligament injuries around the knee and dislocations of the knee joint have been poorly described in the context of multiple trauma [15]. Previous studies have suggested anatomic risk factors for knee injuries, including femoral shaft fractures [16,17], combined femur and tibia fractures [18], patella fractures [19], and acetabular fractures [20].…”
Section: Introductionmentioning
confidence: 99%